Aproveitamento de resíduo agroindustrial de jabuticaba no desenvolvimento de formulação de cookie para a alimentação escolar - Zago, Márcio Fernando Cardoso (2014)
The jaboticaba (Myrciaria cauliflora Berg) is a much appreciated fruit and nutritional importance mainly found in south-central Brazil. Its peel is a by-product discarded in Brazilian agribusiness. The concern about the environmental impacts and the high rate of losses and waste leads to the need to establish means for recovery of such waste. This study aimed to produce flour with peel Jaboticaba, develop biscuit cookie type - enriched with Jaboticaba skin flour instead of wheat flour and oatmeal, analyze technological aspects as much flour as biscuits made from mathematical models and analyze the chemical and functional aspects as much flour as the elaborate cookies. Chemical, microbiological and physical analyzes technological peel blemish in flour and crackers cookie type , according to official methods . All regression models cookies with bark were significant blemish . The water activity of all the cookies found below the recommended limit for the growth of microorganisms . Cookies formulations with higher proportions of bark flour have minor blemish that cookies formulations with higher proportions of oatmeal and wheat flour thicknesses . Moreover , they absorb more water , show lower values of breaking strength and have a decrease in color parameters ( L *, a * and b *) . Cookies made with larger fractions of oatmeal have lower values of specific volume . Formulations with higher percentages of bark jabuticaba flour and wheat flour tend to be more soluble in water . Both the standard cookie and cookie with Jabuticaba bark , selected from the desirability test meal were accepted among children 9-14 years. Embed shell flour blemish on cookies cookie type , increases the health benefits , since this has a high antioxidant capacity and high content of dietary fiber . It is necessary to apply further studies shell flour blemish in food products , since high levels of dietary fiber and bioactive compounds were detected in the peel blemish flour and crackers which were developed in this study.